Cendana (Santalum album ) dan Keanekaragaman Inang Sekundernya Di Daerah Pesisir Kolbano, Nusa Tenggara Timur - Wawo, Albert H.; Abdulhadi, Rochadi (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTSandalwood (Santalum album ) and diversity of their host secondary in Kolbano Village, Lesser Sunda Island. The population of sandalwood (Santalum album ) declined every year because is not cultivated yet by the local people. Inhibiting factors are not possess the knowledge and skills on sandalwood cultivation especially in host plant of sandalwood comprehension. Forest fire and illegal logging lead to lose of flora diversity and deteriorate of sandalwood growth. Result of this research shows that population of sandalwood in Kolbano Village is very low are four plants in Kampong Fatu Un and seven plants in kampong Spaha. In kampong Fatu Un was found eight species plant that compose to unity formation with sandalwood and seven species of them are secondary host of sandalwood. In kampong Spaha was obtained nine species plant that compose to sandalwood formation and seven species of them are secondary host of sandalwood. The highest distribution frequency of plant in two mentioned kampong was got by leucaena (Leucaena glauca) plant with respectively value 51.28% (Fatu Un) and 53.57 % (Spaha), whereas diversity value belong to Simpson Index were 0.71 (Fatu Un) and 0.64 (Spaha).Key words: Sandalwood, host plant, Kolbano village, Lesser Sunda Island